2022
DOI: 10.1111/cas.15637
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric iron chelators for enhancing 5‐aminolevulinic acid‐induced photodynamic therapy

Abstract: 5-Aminolevulinic acid (5-ALA) is an amino acid that can be metabolized into a photosensitizer, protoporphyrin IX (PpIX) selectively in a tumor cell, permitting minimally invasive photodynamic diagnosis/therapy. However, some malignant tumor cells have excess intracellular labile iron and facilitate the conversion of PpIX into heme, which compromises the therapeutic potency of 5-ALA. Here, we examined the potential of chelation of such unfavorable intratumoral labile iron in photodynamic therapy (PDT) with 5-AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Iron chelators boost PDT sensitization, potentially destroying tumor cells by binding iron within cancer cells (mouse colon cancer cells and human gastric cancer cells) and forming active compounds. This process leads to the generation of reactive oxygen species, further augmented by VC [81]. In cancer photothermal therapy, VC is primarily used in conjunction with photothermal materials and nanoparticles for treatment.…”
Section: The Application and Impact Of Vc In Photothermal/photodynami...mentioning
confidence: 99%
“…Iron chelators boost PDT sensitization, potentially destroying tumor cells by binding iron within cancer cells (mouse colon cancer cells and human gastric cancer cells) and forming active compounds. This process leads to the generation of reactive oxygen species, further augmented by VC [81]. In cancer photothermal therapy, VC is primarily used in conjunction with photothermal materials and nanoparticles for treatment.…”
Section: The Application and Impact Of Vc In Photothermal/photodynami...mentioning
confidence: 99%
“…It has been demonstrated that CP94 is more effective at increasing PpIX build-up compared to other iron chelators, such as deferoxamine (DFO) and ethylenediaminetetraacetic acid (EDTA) [ 19 ]. However, to our knowledge, it is yet to be evaluated in comparison to the new polymeric DFO iron-chelating agent that has recently been developed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%